Pemahaman Konseptual tentang Hukum Administrasi Negara dalam Konteks Ilmu Hukum - Nasution, Bahder Johan (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2007)
In a broad sense, Public Administration is often defined as all states’ activities in implementing their political powers, while in the narrow sense, it is an executive activity in implementing governance. These definitions implied that the meaning of ’administration’ in Public Administration Law differ from that of ’administration’ in the science of Public Administration. This article will describe the difference between these two terms in public administration. Kata Kunci: Negara, Adminsitrasi Negara, Ilmu Administrasi Negara, Hukum Tata Negara, Hukum Administrasi Negara.